Review on HIV AIDS - Mohapatra, Abhijita; Sahoo , Debasis (International Journal of Psychosocial Rehabilitation, 2019)
HIV/AIDS has consistently been one of the most completely worldwide of infections. The human immunodeficiency infection (HIV) is a virus that causes HIV disease and AIDS. AIDS is a condition in people wherein dynamic disappointment of the resistant framework permits hazardous contaminations and diseases to flourish. Disease with HIV happens by the exchange of blood, semen, vaginal liquid, bosom milk. Inside these organic liquids, HIV is available as both free infection particles and infection inside contaminated safe cells. HIV taints indispensable cells in the human invulnerable framework, for example, aide CD4 T cells, macrophages. HIV contamination prompts low degrees of T cells through various components, including proptosis of tainted T cells. The side effects of AIDS are basically the aftereffect of conditions that don't regularly create in people with sound safe frameworks. The greater part of these conditions are pioneering contaminations brought about by microbes, infections, growths and parasites that are ordinarily constrained by the components of the invulnerable framework that HIV harms. At the point when condoms are utilized reliably by a couple wherein one individual is tainted, the pace of HIV disease is under 1% every year. There is some proof to propose that female condoms may give an identical degree of security.